2004
DOI: 10.1002/cphc.200300931
|View full text |Cite
|
Sign up to set email alerts
|

Two‐ and Three‐Dimensional Molecular Organization of Schiff‐Base Derivatives

Abstract: We have designed and synthesized a series of Schiff base derivatives, and studied their structural features in two-dimensional (2D) and three-dimensional (3D) states by combining scanning tunneling microscopy (STM) and X-ray diffraction experiments. The Schiff-base derivatives with short alkyl chains crystallize easily, which allows a detailed structural analysis by X-ray diffraction. Due to the strong adsorbate-substrate interactions, those bases with long alkyl chains easily form 2D assemblies on highly orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 85 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…Among various classes of molecules examined, [22][23][24] one of the first and most widely studied are azobenzene-based liquid crystals, 25 and in particular 4-(n-alkyl)-4 0 -cyanobiphenyl (nCB) mesogenic (Fig. 4a).…”
Section: Molecules With a Symmetry Axismentioning
confidence: 99%
“…Among various classes of molecules examined, [22][23][24] one of the first and most widely studied are azobenzene-based liquid crystals, 25 and in particular 4-(n-alkyl)-4 0 -cyanobiphenyl (nCB) mesogenic (Fig. 4a).…”
Section: Molecules With a Symmetry Axismentioning
confidence: 99%
“…9 The combination of three-dimensional, single crystal X-ray structure determinations with STM investigations of two-dimensional monolayers, or a comparison of results from independent studies, is one means of developing an understanding of the processes that control self-assembly in the bulk crystal and self-organisation on surfaces. [10][11][12][13][14][15][16][17][18][19][20][21][22] Where a threedimensional structure is composed of layers, it is reasonable to anticipate that the lamellar motifs may be replicated on a surface. However, the epitaxial effect of the substrate may induce a different lamella-ordering (for example, alkyl-tailed dodecathiophene) 17 dependent upon the relative strengths of the substratem-adsorbate or adsorbate-adsorbate interactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, our previous studies have shown that 7 does not form an ordered structure at liquid-HOPG interface, presumably due to its too low surface affinity caused by the non-planar molecular geometry. 16 In the literature comparisons for the 2D and 3D structures are mostly provided for organic compounds 20,[24][25][26][27][28][29][30][31][32][33][34][35] and only a very limited number of metal complexes, namely ferrocenes, diferrocenes and a Zn salophen complex with a coordinated pyridine, 17,36,37 have been studied in this context. In many cases the physisorbed monolayers could be derived from the 3D crystal packings when certain structural differences were considered, 17,20,[24][25][26][27]30,32,33,[35][36][37] but several opposing cases also exist.…”
Section: D Structures and Their Comparison With 3d Structuresmentioning
confidence: 99%
“…In many cases the physisorbed monolayers could be derived from the 3D crystal packings when certain structural differences were considered, 17,20,[24][25][26][27]30,32,33,[35][36][37] but several opposing cases also exist. [27][28][29]31,34…”
Section: D Structures and Their Comparison With 3d Structuresmentioning
confidence: 99%
See 1 more Smart Citation